Liposomes: structure, composition, types, and clinical applications. Issue 5 (May 2022) - Nsairat, Hamdi; Khater, Dima; Sayed, Usama; Odeh, Fadwa; Al Bawab, Abeer; Alshaer, Walhan
Abstract: Liposomes are now considered the most commonly used nanocarriers for various potentially active hydrophobic and hydrophilic molecules due to their high biocompatibility, biodegradability, and low immunogenicity. Liposomes also proved to enhance drug solubility and controlled distribution, as well as their capacity for surface modifications for targeted, prolonged, and sustained release. Based on the composition, liposomes can be considered to have evolved from conventional, long-circulating, targeted, and immune-liposomes to stimuli-responsive and actively targeted liposomes. Many liposomal-based drug delivery systems are currently clinically approved to treat several diseases, such as cancer, fungal and viral infections; more liposomes have reached advanced phases in clinical trials. This review describes liposomes structure, composition, preparation methods, and clinical applications. Abstract : Liposomes; Phospholipids; Lamellarity; Stealth liposomes; Vaccinations.